Pancake frog in the bog: Chronology and Paleobiogeography of Pipidae (Anura) diversification - (:unkn) unknown (My University, 2022)
Pipids possess one of the best fossil record among anurans, starting during the mid-Cretaceous. Although several occurrences are known in Europe, Pipidae diversified in Gondwana (Africa and South America), where their extant representatives still live. This diversification has traditionally been dated to lower Late Cretaceous, likely linked to the final opening of the Atlantic Ocean. However, several uncertainties persist on the chronology of the diversification around the Early/ Late Cretaceous boundary. The study of this diversification is based on a novel phylogenetical approach. This approach combines detailed stratigraphic data and the "Fossilized Birth-Death Process" (FBD) model of diversification and fossilization. This method produces density probabilities of divergence time for each node within the phylogenetic tree. Our analyses suggest that Pipidae emerged between the Aptian (Early Cretaceous) and the Cenomanian (Late Cretaceous), between 126 and 95 million years ago, depending on the topology used and the attribution of several fossils to Pachycentrata taqueti. This result is compatible with molecular analyses. Our results suggest an intense evolutionary radiation of Pipidae during the 10 million years that followed its origin. This radiation yielded numerous south American and African taxa during the Late Cretaceous and Paleogene. This radiation also indicates that a terrestrial link between Africa and South America was maintained until the end of the Cenomanian. Furthermore, these results suggest long ghost lineages for some extant pipid lineages (including those of Pipa and Hymenochirus), some of which originated during the Cretaceous.
Keywords: African Research